A Matter of Perspective: Exploring Wearable Personal Cameras as a Reflection Tool for Undergraduate Recreation Leadership Students. Issue 2 (1st September 2017) - Mainieri, Tracy L.
Abstract: Students in a 100-level recreation leadership class facilitated two leadership experiences that were video recorded using both a stationary camera and a wearable personal camera. The students used these videos to inform their reflections on their own facilitation practice. A multimethod approach was employed to identify the utility of wearable personal cameras as an educational tool and to analyze student attitudes toward use of wearable personal cameras and traditional cameras as reflection tools. Students in this study reported that the overall video reflection process was helpful, if uncomfortable, and that the two video camera perspectives supported their reflection in different ways. Further, three quarters of the students reported that they found the participant perspective, provided by the wearable personal camera, as the most useful to their reflection processes. The study offered an opportunity to explore how wearable personal cameras could best be incorporated into student reflection experiences.